Flake LABU KUNING (cucurbita moschata) DENGAN KADAR VITAMIN A TINGGI (Pumpkin (cucurbita moschata) flake with high-vitamin a content) - Latifah, Ir; Susilowati, Titi; Erlita, Tri Rini (UPN VETERAN JAWA TIMUR, 2010)
Flake is a type of breakfast , ready meals and golden brown with a crunchy texture. In general, flake were made from wheat flour or from starch tubers like tapioca starch. Pumpkin has vitamin A and high fiber content. Therefore flakes may be added starch and materials developers Sodium bicarbonate (NaHCO3) is expected to assist the process of gelatinization perfectly until the flakes produced porous and crisp.This research aims to study the effect of the proportion of pumpkin and tapioca flour with the addition of sodium bicarbonate to the flakes to obtain flake with acceptable quality. The methods are factorial design which arranged completely randomized and each of two treatment combination was replicated three times. The first factor is the proportion of pumpkin flour: tapioca (60: 40: 65: 35: 70: 3;) g and the second factor was the concentration of sodium bicarbonate (0.25, 0.50, 0.75)%. The best results were getted with the proportion of pumpkin flour: tapioca flour(65: 35) g with the addition of 0.50% sodium bicarbonate to produce flakes with water content 7.56%, starch 43.23%, fiber 8.03%, β-carotene 33.74 μ g / g, 30.11% rehydration capacity and texture of 0.27 kg / cm, while the method of ranking organoleptic texture values obtained 91 and 86 colors (highly preferred) and a sense of 71 (less preferable).Key word: Flakes, pumpkin, starch, tapioka, β karoten